Draft interdisciplinary guidelines for diagnosis, methods for estimation of the degree of activity, for evaluation of therapeutic efficacy, and for use of biological agents in patients with concomitant immunoinflammatory diseases (psoriasis, psoriatic arthritis, Crohn's disease) - D. I. Abdulganieva; A. L. Bakulev; E. А. Belousova; L. F. Znamenskaya; T. V. Korotaeva; L. S. Kruglova; M. M. Kokhan; A. M. Lila; V. R. Khairutdinov; I. L. Khalif; M. M. Khobeish (Современная ревматология)
Due to that one patient may be at high risk for developing several immunoinflammatory diseases (psoriasis, psoriatic arthritis (PsA), and Crohn's disease (CD)), their early diagnosis and adequate therapy are extremely relevant. The Interdisciplinary Working Group that includes experts in rheumatology, gastroenterology and dermatology has developed draft guidelines for early diagnosis, methods for activity assessments and for indications for the use of biological agents in patients with concomitant immunoinflammatory diseases (psoriasis, PsA, and CD). In accordance with the decision adopted by the Council of Experts and with the results of a discussion with experts from different regions of the Russian Federation, further steps will be undertaken to validate the guidelines.